Crisis prevention in sub-Saharan Africa Agriculture: the key to the employment challenge - Losch, Bruno (Perspective, 2012)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"In sub-Saharan Africa, 330 million young people will enter the job market over the next 15 years. That is equivalent to the current population of the United States. This influx could be a catalyst for development, provided there is growth that creates employment. Otherwise, there will be major political risks for Africa and the rest of the world. Yet African economies remain predominantly engaged in agriculture and international competition leaves little scope for rapid economic diversification. Jobs will therefore need to be created on a massive scale in agriculture and the rural sector, especially given that around 200 million of these new workers will live in rural areas. To address this challenge, as well as that of food security, there is an urgent need to establish areas of priority action aimed at reaching the largest number of people possible. This will mean focusing on family farming, supporting the development of food crops and stepping up rural diversification by strengthening the sustainability of local economies. "}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"In sub-Saharan Africa, 330 million young people will enter the job market over the next 15 years. That is equivalent to the current population of the United States. This influx could be a catalyst for development, provided there is growth that creates employment. Otherwise, there will be major political risks for Africa and the rest of the world. Yet African economies remain predominantly engaged in agriculture and international competition leaves little scope for rapid economic diversification. Jobs will therefore need to be created on a massive scale in agriculture and the rural sector, especially given that around 200 million of these new workers will live in rural areas. To address this challenge, as well as that of food security, there is an urgent need to establish areas of priority action aimed at reaching the largest number of people possible. This will mean focusing on family farming, supporting the development of food crops and stepping up rural diversification by strengthening the sustainability of local economies. "}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">In sub-Saharan Africa, 330 million young people will enter the job market over the next 15 years. That is equivalent to the current population of the United States. This influx could be a catalyst for development, provided there is growth that creates employment. Otherwise, there will be major political risks for Africa and the rest of the world. Yet African economies remain predominantly engaged in agriculture and international competition leaves little scope for rapid economic diversification. Jobs will therefore need to be created on a massive scale in agriculture and the rural sector, especially given that around 200 million of these new workers will live in rural areas. To address this challenge, as well as that of food security, there is an urgent need to establish areas of priority action aimed at reaching the largest number of people possible. This will mean focusing on family farming, supporting the development of food crops and stepping up rural diversification by strengthening the sustainability of local economies.